Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fmed.2020.00052
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values for the Short Physical Performance Battery (SPPB) and Their Association With Anthropometric Variables in Older Colombian Adults. The SABE Study, 2015

Abstract: Background: The short physical performance battery (SPPB) is a physical performance test of lower extremity function designed for non-disabled older adults. We aimed to establish reference values for community-dwelling Colombian adults aged 60 years or older in terms of (1) the total score; (2) the three subtest scores (walking speed, standing balance performance, and five times sit-to-stand test); and (3) the time to complete the five times sit-to-stand test, s and the walking speed test. Additionally, we sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 43 publications
4
35
0
8
Order By: Relevance
“…Our findings agree with a Norwegian study which reported ceiling effects of SPPB, across age groups 40–80+ years [ 3 ]. However, such a ceiling effect of SPPB was not observed in Colombian adults aged > 80 years, with 19.8% of males and 7% of females with an SPPB score of 10–12 [ 4 ]. Across ages 40–80+ years, mean SPPB scores in men and women were similar between our study participants and Norwegian adults [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings agree with a Norwegian study which reported ceiling effects of SPPB, across age groups 40–80+ years [ 3 ]. However, such a ceiling effect of SPPB was not observed in Colombian adults aged > 80 years, with 19.8% of males and 7% of females with an SPPB score of 10–12 [ 4 ]. Across ages 40–80+ years, mean SPPB scores in men and women were similar between our study participants and Norwegian adults [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity for each optimal cut-off value and corresponding 95% confidence intervals were reported. Age- and sex-specific smoothed centile curves for GS and STS were generated using standard analytical Lambda Mu Sigma (LMS) method with LMS ChartMakerPro v2.54 (The Institute of Health, London, United Kingdom) [ 4 , 20 – 22 ]. A value of p < 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…GS in the 3 meters test is not a routingly used and this results may underestimated speed (48). However, we do not consider that it biases our results as has been used in previous works (12,18). Nevertheless, the SABE Colombia study has the largest sample of Latin American older adults, providing to our analyses a good statistical power.…”
Section: Discussionmentioning
confidence: 93%
“…Estimates for impaired balance or coordination are 8-14% at 60-69 years, 16-17% at 70-79 years, and 39-46% at 80+ years [14,15], 16% at 60+ years [13] and 28% at 65+ years [16]. Other studies have also report that women have higher prevalences of impairment [22] and that prevalence of weakness and impaired balance increase markedly with age [7,9,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…prevalence of fatigue in multiple sclerosis [4]), there have been relatively few population-based studies. Notable exceptions include studies of population prevalence of weakness in Brasil [5], USA [6][7][8] and Ecuador [9]; fatigue in Norway [10], England [11] and USA [12]; and impaired balance and coordination in Brasil [13], Norway [14], Colombia [15] and the USA [16]. Nonetheless, with the possible exception of estimates of the prevalence of weakness, estimates of the prevalence of specific motor impairments are sparse.…”
Section: Introductionmentioning
confidence: 99%